2012
DOI: 10.1002/cncr.27501
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation in patients with unilateral vestibular schwannoma who undergo stereotactic radiosurgery

Abstract: BACKGROUND:The objective of this study was to identify the prognostic factors for hearing preservation that would allow the more accurate stratification of patients who undergo stereotactic radiosurgery (SRS) for unilateral, sporadic vestibular schwannoma (VS). METHODS: In total, 119 patients with VS who had serviceable hearing underwent SRS as primary treatment. The mean (AEstandard deviation) patient age was 48 AE 11 years, and the mean (AEstandard deviation) follow-up duration was 55.2 AE 35.7 months. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It well corresponds to results reported in the recent literature ( Table 1 ). 1 7 , 9 , 10 , 14 , 15 , 18 , 19 , 22 , 34) Of note, there is some evidence that impact of the cochlear dose on the hearing preservation after GKS of vestibular schwannomas may be not as strong as usually considered. First, in several studies applied multivariate statistical analysis did not reveal independent association between loss of serviceable hearing and cochlear dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It well corresponds to results reported in the recent literature ( Table 1 ). 1 7 , 9 , 10 , 14 , 15 , 18 , 19 , 22 , 34) Of note, there is some evidence that impact of the cochlear dose on the hearing preservation after GKS of vestibular schwannomas may be not as strong as usually considered. First, in several studies applied multivariate statistical analysis did not reveal independent association between loss of serviceable hearing and cochlear dose.…”
Section: Discussionmentioning
confidence: 99%
“…First, in several studies applied multivariate statistical analysis did not reveal independent association between loss of serviceable hearing and cochlear dose. 4 , 14 , 18 , 21 , 22) Second, in cases of other cerebellopontine tumors, such as meningiomas 35) and facial nerve schwannomas, 36) hearing loss after GKS is relatively rare despite frequent delivery of the cochlear doses in excess of 7–10 Gy, which is roughly 2–2.5 times greater than “safe dose” of 4 Gy recommended for optimal audiological outcome after radiosurgery of vestibular schwannomas. 34) It suggests that hearing deterioration after irradiation might be, in fact, multifactorial, but its actual causes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial nerve function was measured using the HB scale. Hearing function was classified according to the Gardner-Robertson hearing scale (GR grading) into serviceable (GR I and II) and nonserviceable (GR III, IV, and V) [10]. Patients with hearing function GR I and II were followed up for hearing preservation.…”
Section: Methodsmentioning
confidence: 99%
“…Success rate is over 90%, but has considerable complication rate, whereas some infrequent malignant transformations have been referred. [3][4][5][6] Surgical removal, reserved for larger vestibular schwannomas over 2.5 cm, is associated with significant functional morbidity (hearing loss, cranial nerves paresis, unsteadiness and headaches), lower quality of life and even mortality. 7 Many studies have shown that a big proportion of acoustic neuromas remain stable in time in terms of size as well as in terms of symptom severity.…”
Section: Introductionmentioning
confidence: 99%